Zum Gedenken an Dorothee Sölle - Grünberg, Wolfgang; Weiße, Wolfram (Hamburger Universitätsreden Neue Folge, 2004)
This volume brings together the speeches given at the academic commemoration ceremony at the University of Hamburg on 27 April 2004. They were supplemented by a sermon by Dorothee Sölle and three exemplary testimonies as an echo of her death.